1863 Del. Laws 365 - (:unkn) unknown (My University, 1863)
An Act to Amend Chapter 55 of the Revised Code of the State of Delaware, Entitled "For The Protection Of Fish, Oysters and Game," chap. 328, § 10: Prohibited hunting in the state by anyone who is not a citizen of Delaware. Prohibited the hunting of any fish, wild goose, wild duck, or other wild fowl. Violators guilty of a misdemeanor and fined not less fifty, nor more than one hundred dollars. Any boat or vessel, apparell, furniture, gun, decoy geese, or decoy ducks shall be forfeited.
Keywords: HUNTING REGULATION